Some Notes on the Genesis of Čep's Autobiographical Essay My Sister Anxiety - Zatloukal, Jan (Bohemica Olomucensia, 2015)
My Sister anxiety, an autobiography of Jan Čep written first-hand in French, was the author's last attempt - fruitless - to gain the French public. It was published by the Christian Academy in Rome only after he died. Since it was issued in 1975 for the first time, some inaccuracies or even errors were spread over the origins of this posthumous autobiography of Čep. Thanks to a detailed research of the sources (an inedited diary, a type-written version of the French original), this paper rectifies these errors and helps to clarify the information on the genesis of My Sister anxiety, the structure of the manuscript and its dating, and the status of this piece of literature itself.
Keywords: Čep's autobiography; My Sister Anxiety; diary sources; genesis of a literary work; manuscript